2017
DOI: 10.19027/jai.16.2.268-276
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination in Nile tilapia broodstock with whole cell vaccine and disease resistance in its fry against Aeromonas hydrophila

Abstract: The aim of this study was to analyze the effectivity of vaccination in Nile tilapia broodstock with whole cell vaccine and disease resistance in fry tilapia against Aeromonas hydrophila. Tilapia Nirwana strain that used for this had average body weight of 185±13.23 g and were maintained in ponds sizing of (2.5×2.5×1 m 3 ). Vaccinations that has been done through intraperitoneal injection using dose of 0.1 mL/fish, meanwhile the fish for control was injected by phosphate buffered saline (PBS). This study used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Indicators determining the health status of fish in the form of haematological parameter can be obtained by observing blood properties (Abu‐Elala, Samir, Wasfy, & Elsayed, ; Silva et al, ; Sukenda, Carman, Rahman, Hidayatullah, & Yumaidawati, ; Sukenda, Rahman, et al, ). The observations of blood properties (Table ) showed that the total leukocytes, phagocytic activity and respiratory burst experienced a significant increase between vaccinated broodstock using polyvalent vaccine compared with unvaccinated broodstock.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indicators determining the health status of fish in the form of haematological parameter can be obtained by observing blood properties (Abu‐Elala, Samir, Wasfy, & Elsayed, ; Silva et al, ; Sukenda, Carman, Rahman, Hidayatullah, & Yumaidawati, ; Sukenda, Rahman, et al, ). The observations of blood properties (Table ) showed that the total leukocytes, phagocytic activity and respiratory burst experienced a significant increase between vaccinated broodstock using polyvalent vaccine compared with unvaccinated broodstock.…”
Section: Discussionmentioning
confidence: 99%
“…The observations of blood properties (Table ) showed that the total leukocytes, phagocytic activity and respiratory burst experienced a significant increase between vaccinated broodstock using polyvalent vaccine compared with unvaccinated broodstock. Total leukocytes in vaccinated broodstock experienced a significant increase compared with unvaccinated broodstock (Abu‐Elala et al, ; Sukenda et al, ). The body's response to recognize antigen was marked by increased leukocytes which can stimulate the formation of antibody (Hardi, Harris, & Lusiastuti, ; Purwanti & Sudaryono, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the haemoglobin and haematocrit percentage in vaccinated sh did not show a signi cant different compared to the unvaccinated sh after immunization. Sukenda [43] also documented that the haemoglobin and haematocrit percentage of vaccinated tilapia were not signi cantly different from unimmunized sh. Once again, both haemoglobin and haematocrit level of immunized tilapia was increased following infection with S. iniae and A. hydrophila, which was also observed in immunized Nile tilapia after infection with A. hydrophila [44].…”
Section: Discussionmentioning
confidence: 93%